2018
DOI: 10.1371/journal.pone.0202942
|View full text |Cite
|
Sign up to set email alerts
|

PNPLA3 p.I148M and TM6SF2 p.E167K variants do not predispose to liver injury in cholestatic liver diseases: A prospective analysis of 178 patients with PSC

Abstract: BackgroundThe adiponutrin (PNPLA3) p.I148M and transmembrane 6 superfamily member 2 (TM6SF2) p.E167K variants represent major genetic risk factors for progressive liver injury in nonalcoholic fatty liver disease (NAFLD), alcoholic liver disease (ALD) and chronic viral hepatitis. The aim of this study was to find out whether these variants have a detrimental impact on the progression of chronic liver disease in patients with prolonged cholestasis induced by primary sclerosing cholangitis (PSC).MethodsWe prospec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
1
10
0
Order By: Relevance
“…From these, 129 articles were selected for full‐text assessment. Ultimately, 25 studies 12,17–40 were included in this meta‐analysis, containing 17 452 PSC patients. The proportion of female patients was 37.1% (95% CI 35.1–39.1%).…”
Section: Resultsmentioning
confidence: 99%
“…From these, 129 articles were selected for full‐text assessment. Ultimately, 25 studies 12,17–40 were included in this meta‐analysis, containing 17 452 PSC patients. The proportion of female patients was 37.1% (95% CI 35.1–39.1%).…”
Section: Resultsmentioning
confidence: 99%
“…6、ALD represents the alcoholic fatty liver disease. M.Krawczyk [9] 2017 Kleiner Score case 68/20/2 control 164/38/3 0-1 2-3 N.Akuta [10] 2016 Brunt Score case 41/13/1 control 63/20/1 0-2 3-4 B. Kruk [11] 2018 Diagnostic criteria for cirrhosis case50/5/0 control 107/16/0 No YES C.Manchiero [12] 2017 Metavir Score case 46/12/0 control 215/17/0 0-2 3-4 U.Vespasiani-Gentilucci [13] 2018…”
Section: Search Resultsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted October 14, 2020. ; https://doi.org/10.1101/2020.10.11.20210690 doi: medRxiv preprint in patients M.Krawczyk [9] 2017 Kleiner Score case 68/20/2 control 164/38/3 0-1 2-3 N.Akuta [10] 2016 Brunt Score case 41/13/1 control 63/20/1 0-2 3-4 B. Kruk [11] 2018 U.Vespasiani-Gentilucci [13] 2018…”
Section: Characteristics Of the Included Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“… 35 In male patients with PSC with bile duct stenosis requiring intervention, the PNPLA3 I148M variant may be a risk factor for reduced survival 36 while another study found no impact. 37 Knockdown/inhibition of PNPLA3 variants is currently receiving considerable attention as novel treatment strategy for NASH. 38 Variants of the ABCB4 gene encoding the hepatobiliary phosphatiylcholine floppase not only confer risk of bile duct injury and cholestatic liver disease by altering bile toxicity, 39 but large-scale whole-genome sequencing uncovered a common ABCB4 variant as a general risk factor for elevated aminotransferases and higher impact variants as potential determinants of early-onset gallstone disease, cholestasis of pregnancy, liver cirrhosis and hepatobiliary cancer.…”
Section: Shared Pathogenetic Principles As Targets For Therapeutic Interventionsmentioning
confidence: 99%